If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -3x + -113 = 69 Reorder the terms: -113 + 10x + -3x = 69 Combine like terms: 10x + -3x = 7x -113 + 7x = 69 Solving -113 + 7x = 69 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '113' to each side of the equation. -113 + 113 + 7x = 69 + 113 Combine like terms: -113 + 113 = 0 0 + 7x = 69 + 113 7x = 69 + 113 Combine like terms: 69 + 113 = 182 7x = 182 Divide each side by '7'. x = 26 Simplifying x = 26
| 3(4x+3)-2=12x+7 | | 16x=15(x+1) | | 4x-24=6x-27 | | -3x=-y-5 | | -4(x+4)=16 | | 46j+18-19j=-28 | | 30-12z=-18 | | x(7*4)=62+9x | | 2x+6=2/3(3x+9) | | 30-12=-18 | | 5x+3-2x=30 | | y^3=216 | | 2x-11=7x+4 | | 6x-4(-4+3)=186 | | (9x+3)(8x^2+5x+3)= | | c-3=5 | | 2=4r-14 | | 2x+2=-2 | | 3+(-5)= | | 48x-3x^2=0 | | x^2+9+20=0 | | 5x-8=-12 | | 3.5+0.9=x | | 8[6(-2x-9)]=80x+408 | | (x+2)(3x-1)-3(x-1)(x+1)+3x=-1 | | 3.5+0.9= | | a/4+a/6+a/8=13 | | 4z^3+3z^2-10z=0 | | .667(x-4)=.33(.5p+3)+6 | | .6m+.25=m-.25 | | 15t/4-30=5t/12 | | 36=x+8x |